Sankofa - Onuzo, Chibundu (Catapult, 2021)
A funny, gripping and surprising story of a mixed-race British woman who goes in search of the African father she never knew, by award-winning author Chibundu Onuzo. Anna grew up in England with her white mother and knowing very little about her African father. In middle age, after separating from her husband and with her daughter all grown up, she finds herself alone and wondering who she really is. Her mother's death leads her to find her father's student diaries, chronicling his involvement in radical politics in 1970s London. She discovers that he eventually became the president - some would say the dictator - of Bamana in West Africa. She also discovers that he is still alive. She decides to track him down and so begins a funny, painful, fascinating journey, and an exploration of race, identity and what we pass on to our children.